2018
DOI: 10.1097/tgr.0000000000000195
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Adding Transcutaneous Neuromuscular Electrical Stimulation (VitalStim) to Traditional Therapy for Poststroke Dysphagia

Abstract: Background: Dysphagia may delay the functional recovery and substantially affects the quality of life after stroke, mainly if left untreated. Electrical stimulation has been reported as a treatment for pharyngeal dysphagia in recent studies, but the therapeutic effect of neuromuscular electrical stimulation (VitalStim) therapy lacks convincing supporting evidence and needs further clinical investigation. Methods: A total of 135 subjects were randomly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(51 citation statements)
references
References 23 publications
0
51
0
Order By: Relevance
“…This observation calls for further improvement in the management of dysphagic patients. Recent studies indicate that functional magnetic or electrical stimulation may improve dysphagia as compared to conventional swallowing therapy, but these results need to be confirmed by larger studies [ 32 , 33 ]. There could be a need for such novel approaches, as swallowing dysfunction may persist in many patients for a longer time [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This observation calls for further improvement in the management of dysphagic patients. Recent studies indicate that functional magnetic or electrical stimulation may improve dysphagia as compared to conventional swallowing therapy, but these results need to be confirmed by larger studies [ 32 , 33 ]. There could be a need for such novel approaches, as swallowing dysfunction may persist in many patients for a longer time [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…NMES is effective in muscle strengthening, prevention of muscle atrophy, and neuromuscular re-education2, 3 ) . However, most studies have reported applying it on the swallowing-related muscles located on the front side of the neck in patients with pharyngeal dysphagia to examine the effects on swallowing function4, 5 ) . Therefore, there is insufficient evidence on the effects of NMES on patients with oral phase dysphagia accompanied by CFP.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that NMES significantly enhanced the recovery of the swallowing function [28,29]. Li et al [14] examined the effectiveness of a swallowing therapy in 118 patients for 4 weeks and reported that the combination of NMES and a traditional dysphagia therapy improved the swallowing function than the NMES-only treatment or the traditional rehabilitation therapy only treatment. Bulow et al [28] compared the effects of traditional swallowing disorder therapies with those of NMES, using a randomized controlled trial (RCT) design and showed that there was no significant difference between them.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have consistently shown that NMES is effective for compensatory strategies and rehabilitation therapy [11,12]. On the contrary, several studies reported that NMES was not effective [13][14][15][16][17]. Therefore, further studies are needed to verify the effectiveness of NMES.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation